The expansion and performance of national newborn screening programmes for cystic fibrosis in Europe - Barben, Jürg; Sommerburg, Olaf (Journal of cystic fibrosis, 2017)
Background: Newborn screening (NBS) for cystic fibrosis (CF) is a well-established public health strategy with international standards. The aim of this study was to provide an update on NBS for CF in Europe and assess performance against the standards. Methods: Questionnaires were sent to key workers in each European country. Results: In 2016, there were 17 national programmes, 4 countries with regional programmes and 25 countries not screening in Europe. All national programmes employed different protocols, with IRT-DNA the most common strategy. Five countries were not using DNA analysis. In addition, the processing and structure of programmes varied considerably. Most programmes were achieving the ECFS standards with respect to timeliness, but were less successful with respect to sensitivity and specificity. Conclusions: There has been a steady increase in national CF NBS programmes across Europe with variable strategies and outcomes that reflect the different approaches.